Keanekaragaman Jenis Tumbuhan Pewarna Alami sebagai Bahan Tenun Ikat di Sekitar Kawasan Hutan Lindung Pisok (Studi Kasus di Desa Rura, Kecamatan Reok Barat, Kabupaten Manggarai) - Filemon Bogos; Ludji Michael Riwu Kaho; Wilhelmina Seran (Wana Lestari, 2024)
This research aims to determine the level of diversity of dye plant species as weaving materials around Pisok Protected Forest Area, Rura Village, West Reok District, Manggarai Regency. This research was conducted around Pisok Protected Forest Area, Rura Village, West Reok Subdistrict, Manggarai Regency which was conducted for 1 month from December 2023 to January 2024. This research used purposive sampling method with data analysis using descriptive qualitative and descriptive quantitative analysis. Data were processed using the vegetation analysis formula and the Shannon-Wiener diversity formula (H'). Based on the results of vegetation analysis around the Pisok Protection Forest area in Rura Village, it was found that out of a total of 31 plant species, there are 3 plant species that are usually used as natural dyes for ikat woven fabrics, namely Candlenut (Aleuritas moluccana L), Noni (Morinda citrifolia), and Tarum (Indigofera spicata). The level of species diversity (H') around the Pisok Protection Forest area in Rura Village is classified as high and moderate, namely at the tree level of 2.91 including moderate criteria, poles of 3.08 including high criteria, saplings of 2.67 including moderate criteria, and seedlings reaching 2.17 including moderate criteria.